In vitro plantlets from somatic embryos of selected ornamental plants- A new prospect for interior decorations and horticulture industry - Mat Taha, R.; Hasbullah, N.A.; Awal, A. (2009)
Somatic embryogenesis is a multi-step process for the induction of somatic embryogenesis, embryo development, embryo maturation and embryo germination. All plantlets obtained through somatic embryogenesis did not differ phenotypically from the parental clones (Stefaniak, 1994). In this study, several plants such as Gerbera jamesonii, Begonia x hiemalis Fotsch., and Saintpaulia ionantha were successfully regenerated through somatic embryogenesis process. Explants such as leaf, petiole and stem were used to induce somatic embryos from all the plant species. Explant were cultured on Murashige and Skoog (MS) medium supplemented with various types of plant growth regulators such as 6-Benzylaminopurine (BAP), a-Naphthalene acetic acid (NAA), 2, 4-Dichlorophenoxyacetic acid (2,4-0) and Thidiazuron (TDZ). Due to the attractiveness and elegance of in vitro plantlets derived from somatic embryos, they have the potential to be promoted and marketed as interior decorations, scientific handicrafts and further publicized as a new prospect in horticulture industry.